independent from the directrix, the eccentricity is defined as follows:

For a given ellipse:

  • the length of the semi-major axis = $a$

  • the length of the semi-minor = $b$

  • the distance between the foci = $2c$

  • the eccentricity is defined to be $\dfrac{c}{a}$

now the relation for eccenricity value in my textbook is $\sqrt{1- \dfrac{b^{2}}{a^{2}}}$

which I cannot prove.

  • $\begingroup$ The three quantities $a,b,c$ in a general ellipse are related. Do you know how? $\endgroup$
    – Arthur
    Apr 14, 2017 at 19:44
  • $\begingroup$ I thought I did, there's right angled triangle relation but i cant recall it $\endgroup$
    – sarah
    Apr 14, 2017 at 20:35
  • $\begingroup$ Then you should draw an ellipse, mark foci and axes, label everything $a,b$ or $c$ appropriately, and work out the relationship (working through the argument will make it a lot easier to remember the next time). Once you have that relationship, it should be able easy task to compare the two values for eccentricity. $\endgroup$
    – Arthur
    Apr 14, 2017 at 22:31
  • $\begingroup$ Have you ever try to google it? There're plenty resources in the web there!! $\endgroup$ Apr 15, 2017 at 19:40

2 Answers 2


Consider an ellipse with center at the origin of course the foci will be at $(0,\pm{c})$ or $(\pm{c}, 0) $

As you have stated the eccentricity $e$=$\frac{c} {a}$ Note also that $c^2=a^2-b^2$, $c=\sqrt{a^2-b^2} $ where $a$ and $b$ are length of the semi major and semi minor axis and interchangeably depending on the nature of the ellipse

$e=\frac{c} {a}$ =$\frac{\sqrt{a^2-b^2}} {a}$=$\frac{\sqrt{a^2-b^2}} {\sqrt{a^2}}$

$e=\sqrt{\frac{a^2-b^2} {a^2} }$

Can you finish it from there?


For two focus $A,B$ and a point $M$ on the ellipse we have the relation $MA+MB=cst$.

We can evaluate the constant at $2$ points of interest :

  • on the intersection of major axis and ellipse closest to $A$


  • on an intersection of minor axis and ellipse

we have $MA=MB$ and by pythagore $MA^2=c^2+b^2$
Combining all this gives $4a^2=(MA+MB)^2=(2MA)^2=4MA^2=4c^2+4b^2$
$\implies a^2=b^2+c^2$

Please try to solve by yourself before revealing the solution.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.